Understanding Maritime Subjects in Vocational High Schools through Online Learning - Nanang Joko Sulistyono; Suparji Suparji; Theodorus Wiyanto; Ratna Suhartini; Ilham Ilham (Journal of Pedagogi, 2024)
This study explores the effectiveness of online learning for maritime subjects in Indonesian vocational high schools, focusing on how the rapid advancement of information technology has reshaped education in this unique field. Using a quantitative approach with 275 respondents, the research analyzes key factors that influence students' understanding of maritime subjects, such as digital literacy, motivation, and their perceptions of the effectiveness of online learning. The findings indicate moderate levels of both digital literacy and motivation for online learning, with flexibility being the most appreciated benefit. However, challenges related to social isolation were also noted. A predictive model developed during the research accounts for 43% of the variance in comprehension of the subject matter, identifying digital literacy and perceived online learning effectiveness as the strongest predictors. Additionally, the grade level of students significantly influenced their comprehension scores. This study emphasizes the need to integrate digital skills training and to employ engaging instructional strategies to enhance learning outcomes. Future research could investigate the use of immersive technologies, such as virtual reality or simulations, to better support practical skills development in maritime education, ensuring that students are well-prepared for real-world challenges in the maritime industry